An effective, facile, and rapid synthesis of nanosized Mn3O4 using a microwave route - Yadav, Akash; Jha, Ratnesh; Bhatkar, Akash; Kamble, Aditi; Vaishnav, Vishal; Bogalera, Shivamurthy P.; Manikandan, Marimuthu; Nayaka, Girish Praveen; Umbarkar, Shubhangi; Raja, Thirumalaiswamy; Bhatte, Kushal D. (Journal of Nanoparticle Research, 2024)
Microwave-assisted one-pot, one-step, calcination-free synthesis of nanosized Mn3O4 is reported using only benzylamine and manganese acetate. Benzylamine in this protocol plays a vital role for efficient microwave synthesis. This microwave method enables the synthesis of nanosized Mn3O4 in just few hours only in a single step eliminating the need of calcinations of any intermediate. The synthesized nanosized Mn3O4 was analyzed by XRD, HRTEM, EDAX, and Raman spectroscopy. The catalytic and electrochemical properties of as-synthesized Mn3O4 were investigated. In galvanostatic charge-discharge experiments, after 800 cycles, more than 89% capacitance was retained for electrodes made by as synthesized Mn3O4 nanomaterials indicating its very good stability. In the catalytic conversion of cinnamyl alcohol to cinnamaldehyde via oxidation, using as prepared nanosized Mn3O4 as a catalyst, it displays effective catalytic properties. A probable mechanical study of its formation was also envisaged. This synthesis protocol is additive-free, occurs in a short time, is facile, is energy efficient, and eliminates the use of many chemicals. These silent features make these reported protocols economically viable and environmentally benign which adhere to the principles of Green Chemistry.
Keywords: Calcination free; Electrochemical and catalytic properties; Nanosized Mn3O4; Single-step synthesis

Enhanced photocatalytic hydrogen evolution in deionized/natural seawater and removal of organic pollutants using the heterostructure of CuO/Cu2O nanoparticles under visible light - Kangutkar, Raju S.; Walko, Priyanka; Nayaka, Girish Praveen; Nigam, Sandeep; Majumder, Chiranjib; Manjanna, Jayappa (Langmuir, 2026)
Water splitting for hydrogen production and reducing water pollution using solar light are part of the Sustainable Development Goals, which require highly active photocatalytic materials. The heterostructures have demonstrated remarkable photocatalytic advantages in visible light. Herein, we report microwave-assisted green synthesis of CuO/Cu2O nanoparticles using Tridax plant leaf extract. The synthesized nanoparticles were characterized by using PXRD, UV-DRS, Raman spectroscopy, XPS, PL, TRPL, FE-SEM, HR-TEM, BET, and photocurrent. The photocatalytic water splitting performance of CuO/Cu2O and CuO was measured under visible light (lambda >= 420 nm) irradiation using methanol as a sacrificial reagent in DI water and natural seawater. The H2 evolution rates in DI water for CuO/Cu2O and CuO are 2043.21 and 970.09 mu mol g-1 h-1 with apparent quantum efficiency (AQE) values of 5.60 and 2.66 %, respectively. In natural seawater, the H2 evolution rates are 2599.29 and 1370.54 mu mol g-1 h-1 with AQE values of 7.12 and 3.75 %, respectively. The rate of H2 evolution slightly increased in natural seawater. Also, the degradation of the methylene blue dye was examined here, and the efficiency of CuO/Cu2O was determined to be 97 % under natural sunlight. Electrocatalytic H2 evolution was also studied here by using linear sweep voltammetry. Tafel slope values for CuO/Cu2O and CuO are 153 and 250 mV dec-1, respectively. The lowest Tafel value of CuO/Cu2O indicates a faster rate of reaction, thereby producing easier charge separation and lowering the electron-hole recombination due to the presence of surface defects, smaller particle size, enhanced crystallinity, and the synergistic effect between Cu2O and CuO.